THE CHOICE OF DRUGS FOR THE TREATMENT OF INFECTIOUS DISEASES IN CHILDREN WITH DRUG ALLERGY - E. B. Pavlova; V. N. Timchenko; N. V. Pavlova; S. L. Bannova; A. V. Fedorovа; O. V. Bulinа; J. K. Khakizimana (Детские инфекции (Москва), 2018)
The article presents the results of clinical observation of 104 children hospitalized in the infectious department and having manifestations of allergies to drugs (medicines) at the prehospital stage or in the hospital. The frequency of allergic reactions to medicines in children with infectious diseases, their characteristics, as well as approaches to the choice of drugs for treatment, as manifestations of allergies, and the underlying disease in children with drug allergies are estimated. It has been shown that antibacterial drugs are a frequent cause of skin allergic reactions in patients with lacunar angina and infectious mononucleosis. In case of allergy to beta-lactams, macrolides and lincosamides serve as an alternative in most cases. As a drug of choice for fighting fever in patients with an acute allergic reaction to drugs, ibuprofen may be recommended, possibly using paracetamol, metamizole sodium.